Sovremennye informacionno-komp'juternye sredstva pri analize sorevnovatel'noj dejatel'nosti - Sevost'janov, I. A.; Cholodkov, Z. K. (Teorija i Praktika fiziceskoj Kul'tury, 2005)
The monitoring of video-recordings of competitive activity is an integral part of construction of an effective training process. Thus the quality of the analysis depends not only on the kind of medium and used technical means, but it also depends directly on the technique of realization of the research.